Virtual Laboratories in Science Education: A Systematic Review of Effectiveness on Conceptual Understanding and Learning Outcomes - Meronda, Devi Apriana; Widarti, Hayuni Retno; Yahmin, Yahmin (Jurnal Pendidikan MIPA, 2025)
Virtual laboratories (VLs) have emerged as a significant innovation in science education, enriching learning experiences, deepening conceptual understanding, and providing more flexible and safer access to experiments. Nevertheless, the implementation of VLs still faces challenges, particularly in developing practical skills and ensuring integration with physical laboratories. This study aims to present a comprehensive review of the impacts, potentials, and limitations of VLs through a systematic literature review. The method employed follows the PRISMA protocol, with Scopus as the primary database. Out of 489 initial articles, only 21 articles met the inclusion and exclusion criteria after the screening process. The analysis was directed toward two main research questions: (1) to what extent does the use of interactive simulation–based virtual laboratories enhance conceptual understanding, and (2) how do students’ learning outcomes compare with those of traditional laboratory practices? The findings revealed that the development of VLs is typically grounded in constructivist approaches and instructional design models that emphasize the creation of interactive experiences that resemble real experiments. Furthermore, the results suggested that students taught using VLs achieve better learning outcomes compared to those taught through traditional methods. VLs have been shown to support improvements in conceptual understanding, laboratory skills, scientific literacy, questioning ability, analytical thinking, and cognitive performance, all of which contribute to strengthening critical thinking skills. Thus, VLs not only serve as a solution to the limitations of physical facilities but also play a crucial role in fostering critical thinking as one of the key competencies of the 21st century.   Keywords: virtual laboratory, science education, and learning outcomes.